PS 10-07 TETRAHYDROBIOPTERIN EFFECTS LEFT VENTRICULAR DIASTOLIC FUNCTION BY UPREGULATING PROTEIN KINASE Cε SIGNALING PATHWAY IN DESOXYCORTICOSTERONE ACETATE-SALT HYPERTENSIVE MICE. (September 2016) - Xu, Han; Wang, Qiong-ying; Ma, Rui-xin; Li, Ning-yin; Li, Xiu-li; Lin, Xin; Zhang, Xiao-wei; Yu, Jing
Abstract : Objective: To identify the influence of tetrahydrobiopterin (BH4)on left ventricular diastolic function and the expression of protein kinase Cε (PKCε) in desoxycorticosterone acetate (DOCA) salt hypertensive mice. Design and Method: Male C57BL/6 mice were divided into operation group and Sham operation. Mice in operation group were resected of the left kidney and implanted DOCA pill in the cervical part, after operation, mice were randomly divided into DOCA group and DOCA+BH4 group. Mice in Sham operation were only separated the left kidney instead of resecting it, and placebo pill was put in the cervical part, after operation, mice were randomly separated into Sham group and Sham+BH4 group. Arterial pressure, echocardigraphy and hemodynamic method were used to investigate the DOCA model establishment, cardiac structure and function on day 21 after operation. The next day cyclic guanosine monophosphate (cGMP), malonaldehyde, BH4 and PKCε were detected by enzyme linked immunosorbent assay, Western-blot or high-Performance liquid chromatography in cardiac tissues of all euthanized mice. Results: Compared to Sham group, systolic blood pressure (SBP) and diastolic blood pressure (DBP) in DOCA group were increased (P < 0.05). E/E', EDPVR and Tau index werei increased in DOCA group when compared with Sham group. After BH4 treatment in DOCA mice. EDPVR and Tau index were reduced.Superoxide dismutase (SOD) and nitric oxide (NO) in DOCA group were reduced when compared with Sham group. After BH4 treatment in DOCA mice, SOD and NO were increased. Compared to Sham group, the protein level of PKCε in DOCA group was decreased (P < 0.05), while it was increased inDOCA+BH4 group as compared with DOCA group (P < 0.05). Conclusions: BH4 had little effect on BP, but it could improve left ventricular diastolic dysfunction in hypertensive mice, which was related to lowering the levels of oxidative stress, increasing amounts of NO by upregulating PKC ε signaling pathway.